Relationship between electromyogram spectrum parameters and the tension-time index during incremental exercise in trained subjects - Chlif, M.; Keochkerian, D.; Temfemo, A.; Choquet, D.; Ahmaidi, S. (Journal of Sports Science & Medicine, 2018)
The inspiratory muscle tension-time index TT0.1 (given by P0.1/PImax x TI/TTOT) could be used to reliably assess inspiratory muscle activity during exercise. So far, the correlation between the TT0.1 and diaphragmatic activity has not been measured and the TT0.1 has not been compared with other measurements of the inspiratory muscle load such as the transdiaphragmatic pressure index or TTdi. In this study we hypothesize that the TT0.1 measuring the mouth is a noninvasive reflection of the electromyographic activity of the diaphragm. We simultaneously measured TT0.1 and surface EMG (SEMG) of 8 trained subjects at rest and during incremental exercise. The curvature of TT0.1 and the root mean square (RMS) follow the same trend during the incremental exercise with a significant correlation between TT0.1 and surface EMG parameters (RMS; r = 0.81 p < 0.001 and MPF; r = 0.80 p < 0.001 respectively). We conclude that TT0.1 measured as s an adequate noninvasive method reflects the diaphragmatic activity during incremental exercise in healthy subjects.